2010
DOI: 10.4104/pcrj.2010.00010
|View full text |Cite
|
Sign up to set email alerts
|

Set-up and pilot of a population cohort for the study of the natural history of COPD and OSA: the PULSAIB study

Abstract: Aims: We describe the set-up of a population-based study focussed on respiratory conditions, and describe a pilot study -the PULmons SAns Illes Balears (PULSAIB) study -aimed at investigating the natural history of COPD, obstructive sleep apnoea (OSA), and other common chronic diseases.Methods: A cross-sectional study was designed to survey two fieldwork areas, one rural and one urban, in the Balearic Islands, Spain. Tests conducted included a questionnaire, spirometry with post-bronchodilator (PBD) test, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(24 reference statements)
0
9
1
Order By: Relevance
“…[3] Data from the Balearic Islands showed similar results, with a prevalence of 12.8% in this age group. [4] Pharmacologic and non-pharmacologic treatments can help to improve COPD control and symptoms and slow down disease progression. [1] In contrast to asthma, where inhaled corticosteroids (ICS) are the main pharmacological treatment, their efficacy and role in the treatment of COPD is less evident.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Data from the Balearic Islands showed similar results, with a prevalence of 12.8% in this age group. [4] Pharmacologic and non-pharmacologic treatments can help to improve COPD control and symptoms and slow down disease progression. [1] In contrast to asthma, where inhaled corticosteroids (ICS) are the main pharmacological treatment, their efficacy and role in the treatment of COPD is less evident.…”
Section: Introductionmentioning
confidence: 99%
“…Some Blue Zones might become extinct. All these factors likely interact and vary in time, making it difficult to study in depth the natural history of diseases in the community, respiratory or other …”
Section: Discussionmentioning
confidence: 99%
“…All these factors likely interact and vary in time, making it difficult to study in depth the natural history of diseases in the community, respiratory or other. 31,32 The forthcoming results of the Genetics of Healthy Ageing (GEHA) project 33 and other ongoing initiatives will be welcome. Furthermore, by engaging older members of the public and older patients in research, the generalizability of research findings will be improved.…”
Section: Discussionmentioning
confidence: 99%
“…OSA is a common respiratory disorder during sleep that characterized by apneas, and associated with a reduction in blood oxygen saturation. Each event of OSA typically lasts 20-40 seconds (18)(19)(20) and caused by obstruction of the upper airways (21). A recent assessment of polysomnography has shown that approximately onequarter to one-half of OSA patients are suffering from PLMD (22,23).…”
Section: Introductionmentioning
confidence: 99%